2023
DOI: 10.1101/2023.01.24.23284869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized Trial Comparing Omicron-Containing Boosters with the Original Covid-19 Vaccine mRNA-1273

Abstract: BackgroundOmicron-containing bivalent boosters are available worldwide. Results of a large, randomized, active-controlled study are presented.MethodsThis phase 3, randomized, observer-blind, active-controlled trial in the United Kingdom evaluated the immunogenicity and safety of 50-μg doses of omicron-BA.1-monovalent mRNA-1273.529 and bivalent mRNA-1273.214 booster vaccines compared with 50-μg mRNA-1273 administered as boosters in individuals ≥16 years. Participants had previously received 2 doses of any autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…As of March 2023, 20 studies were identified for the systematic review (Figure 1) [15,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. A total of nine studies investigated the effectiveness of a BA.5-containing BV, five studies explored a BA.1-containing BV, and two studies examined a BA.1-or BA.5-containing BV (Table 1).…”
Section: A Flowchart Of the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As of March 2023, 20 studies were identified for the systematic review (Figure 1) [15,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. A total of nine studies investigated the effectiveness of a BA.5-containing BV, five studies explored a BA.1-containing BV, and two studies examined a BA.1-or BA.5-containing BV (Table 1).…”
Section: A Flowchart Of the Systematic Reviewmentioning
confidence: 99%
“…Figure 2. Forest plot of the geometric titer against ancestral strains of bivalent and monovalent vaccines[15,16,25,[27][28][29]34,36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was not designed to assess vaccine effectiveness (VE). Though recent data suggest possibly higher VE against Omicron subvariants with bivalent vaccine boosts (Prototype + Omicron BA.4/5, Prototype + Omicron BA.1) compared with the Prototype vaccine, 18 , 39 our findings highlight concerns that variant vaccines are unlikely to keep pace with virus evolution and that other immune correlates of protection beyond antibody responses need to be explored.…”
Section: Discussionmentioning
confidence: 58%
“…Recent data from a large, phase 3, randomized trial in the United Kingdom support these recommendations, wherein the efficacy, immunogenicity, and safety of a booster dose of the original mRNA-based COVID-19 vaccine (mRNA-1273) or variant-containing omicron (BA.1) booster vaccines (mRNA-1273.529 or mRNA-1273.214) administered after any COVID-19 primary vaccination schedule (primarily BNT162b2 or ChAdOx1-SARS-CoV-2 vaccines) were compared. 3 Overall, all mRNA-based vaccine booster regimens induced robust immune responses against omicron BA.1, with COVID-19 incidence numerically lower for the BA.1-containing vaccines than the original vaccine. These data highlight the utility of a heterologous booster regimen for continued protection against COVID-19.…”
mentioning
confidence: 92%